Revisiting business cycle synchronisation in the European Union - Afonso, António (2011)
We assess the business cycle synchronization features of aggregate output in the 27 EU countries using annual data for the period 1970-2009. In particular, we compute measures of synchronisation for private consumption, government spending, gross fixed capital formation, exports and imports. Our results show a rise in synchronization over the full period, and although private consumption is the biggest component of GDP, external demand tends to be a more important determinant of business cycle synchronization.